Comparative evaluation of electronic and radiographic odontometry (Research, Society and Development, 2021)
This study aimed to evaluate the effectiveness of the ROOT ZX electronic apical locator using the radiographic dentistry method, with the aim of verifying whether there was a difference between electronic and radiographic dentometry in relation to the pulp condition: live pulp, dead pulp (with or without periapical injury). Were selected 38 root canals of the teeth of patients of both sexes, attended in the Dentistry course of the State University of Pernambuco. The comparison with the measurements obtained by the apical locator was performed, standardizing the dental coefficients considered correct, that is, at 1 mm from the apical foramen and with an acceptable margin of error of ± 0.5 mm. In the comparative evaluation of the real measurements of the root canals in relation to the apical locator, it was observed that the ROOT ZX presented a percentage of 94,73% of accuracy. Based on the service protocol used, it can be said that the use of the ROOT ZX locator is a highly reliable and accurate device in measuring the actual working length and can be safely used to obtain the actual length of the tooth.